The Sociodrama Method in Learning the Indonesian Proclamation of Independence at High School - Mita Rizki Utami; Ganda Febri Kurniawan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
History education on the Indonesian Proclamation of Independence at the high school level often faces challenges due to predominantly narrative and textual methods, hindering students from deeply internalizing its meaning and actively participating. While various digital media innovations have emerged, their drawbacks include limited two-way interaction, high production costs, and insufficient school infrastructure. This study examines the relevance and effectiveness of the sociodrama method as an innovative alternative. Sociodrama enables students to empathetically experience historical events and figures, fostering active participation, collaboration, and communication, while requiring minimal infrastructure. The successful implementation of sociodrama is largely determined by the teacher's role and readiness as a facilitator, students' preparedness and active involvement, the historical accuracy and quality of the scenario, and a conducive learning environment. Thus, the sociodrama method is expected to enhance student participation, cultivate nationalism, and deepen their understanding of the human dimension within the history of the Indonesian Proclamation of Independence.